1999
DOI: 10.1080/0141192990250508
|View full text |Cite
|
Sign up to set email alerts
|

From Inspection to School Improvement? Evaluating the Accelerated Inspection Programme in Waltham Forest

Abstract: In 1995, the Office for Standards in Education (OFSTED) had the first opportunity to look at a substantial number of inspection reports from across the education system. Using this analysis, the London Boroughs of Waltham Forest and Lambeth were identified as having over 40% of their schools within the category of 'serious weaknesses' or failing'. In direct response to these findings OFSTED announced an accelerated inspection programme for all schools within each borough. This article discusses the main conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(5 reference statements)
0
7
0
1
Order By: Relevance
“…Rosenthal (2004) even identifies a slight decline in student achievement levels in the year of the inspection visit. Hopkins et al (1999) noted that the occasional character of teacher inspection does not contribute to the improvement of the quality of the education provided. Ouston and Davies (1998) researched 55 schools which had been inspected between 1993 and 1996 and found that the impact of the inspection suggested that a change was inconclusive.…”
Section: Impact On School Performancementioning
confidence: 99%
“…Rosenthal (2004) even identifies a slight decline in student achievement levels in the year of the inspection visit. Hopkins et al (1999) noted that the occasional character of teacher inspection does not contribute to the improvement of the quality of the education provided. Ouston and Davies (1998) researched 55 schools which had been inspected between 1993 and 1996 and found that the impact of the inspection suggested that a change was inconclusive.…”
Section: Impact On School Performancementioning
confidence: 99%
“…A recent EUstudy (see Jones et al, in prep) shows how principals in England scored significantly higher on items around unintended strategic responses, particularly on items about refocusing and narrowing the curriculum and teaching and learning strategies to meet inspection criteria, compared to their peers in the Netherlands, Ireland, Sweden, and Austria. School inspections also seem to slow down school development when schools suspend school activities when time is needed to prepare for inspections or had less energy for change after an intense visit (Ouston et al, 1997;Hopkins et al, 1999;Plowright, 2007;Berry, 2012). Nees (2006) reports of concerns about the sustainability of improvements made in six primary schools in Wellington (New Zealand) in response to external review, including recruitment challenges and barriers to learning among their students.…”
Section: Unintended Strategic Behaviourmentioning
confidence: 99%
“…Nees (2006) reports of concerns about the sustainability of improvements made in six primary schools in Wellington (New Zealand) in response to external review, including recruitment challenges and barriers to learning among their students. Hopkins et al (1999) also explain how relationships within schools suffer from the pressure to prepare and undergo an Ofsted inspection (Hopkins et al, 1999), and how the normal running of the school is interrupted during an inspection visit when inspectors for example influence the behaviour and contributions of pupils in lessons (Dean, 1995;Gray and Gardner, 1999).…”
Section: Unintended Strategic Behaviourmentioning
confidence: 99%
“…De dubbele rol van enerzijds 'inspecteur' en anderzijds 'begeleider' wordt in verschillende onderwijssystemen immers als onverenigbaar gepercipieerd (Ehren & Honingh, 2011;Waterman, 2013). Verschillende academici stellen dat scholen die doorgelicht worden, door de angst die zij ervaren op datzelfde moment niet openstaan voor ontwikkeling (Faubert, 2009;Hopkins, Harris, Watling, & Beresford, 1999;MacKinnon, 2010). Voor schoolontwikkeling is het immers cruciaal dat er vertrouwen is en dat een school zich 'open en bloot' durft te tonen aan de inspecteur (Macbeath, 2006;Ouston & Davies, 1998).…”
Section: Conceptueel Kaderunclassified